Approach for Preparation of Bimetallic Palladium-Cobalt Catalysts with Enhanced Electrocatalytic Performance for Methanol Oxidation. Issue 13 (1st January 2016) - Su, Wen; Wang, Tong; Fu, Yingyi; Hu, Jingbo
Abstract : A series of indium tin oxide (ITO) supported palladium-cobalt binary metallic anode catalysts were prepared and used in the methanol oxidation reaction (MOR), which is a key reaction in direct methanol fuel cells (DMFCs), providing superior fuel. The morphology, composition, and electrocatalytic performance of Pd- x -Co/ITO ( x = 5, 10 and 15) catalysts were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), cyclic voltammetry (CV), and chronoamperometric techniques. For comparison, Pd- x /ITO ( x = 5, 10 and 15) catalysts were also tested under the same conditions. Compared with pure Pd nanoparticles on ITO (Pd/ITO), due to the participation of Co as a support, the as-prepared Pd-10-Co/ITO catalyst exhibited a lower onset potential, enhanced electrocatalytic activity, and better durability in the MOR in alkaline media without the use of other oxidants. Moreover, Pd-10-Co/ITO can significantly contribute to cost reduction when used as an anode catalyst for DMFCs.